Is the behaviour a feature that implies evolutionary consequences in the speciation? - Alejandro Correa Rueda (Global Journal of Zoology - Peertechz Publications, 2023)
In birds, similar behaviour decreases in dramatic form the distances among sister lineages. The current classification of the Chilean representatives of the passerine family Rhinocryptidae includes eight species. Moreover, differences between the two lineages of Chilean species of Scytalopus genera, and two subspecies of Scelorchilus. Scelorchilus albicollis albicollis vs. S. a. atacamae; S. rubecula rubecula vs. S.r. mochae, two species of Pteroptochos: P. castaneus and P. tarnii, and two subspecies: P.megapodius megapodius and P.m. atacamae are very scarce. We propose a new methodology based on ecological and behavioural patterns in order to understand the concept of speciation in this group of birds. Our results show how when integrating behaviour and ecological terms as biological traits next to morphological characters of the plumage, allows us to conclude that there is a decrease in the distances among sister lineages in the cluster tree.